Application of Slow Deep Breathing Exercise in Reducing Pain Intensity in Pre-Operative Patients with Lateral Inguinal Hernia Sinistra: Case Study - Suwardi, Suwardi; Nirwan, Nirwan; Rimadeni, Yeni; Oetama, Saiful; Halimatussakdiah, Halimatussakdiah (Poltekkes Kemenkes Aceh, 2024)
Background: Inguinal hernia occurs when there is a protrusion of the contents of a cavity through a weak part of the inguinal gap in the abdominal wall. The occurrence of inguinal hernia is caused by repeated and continuous increase in intra-abdominal pressure. The increase in inguinal hernia cases has now reached 20 million cases, most of which are suffered by late adults to the elderly with the main problem being acute pain and its management through herniotomy. Slow Deep Breathing Exercise is one of the non-pharmacological therapies that is often used to overcome acute pain felt by pre-operative patients. Purpose: To provide an overview of the application of slow deep breathing in the management of acute pain in preoperative patients with left lateral inguinal hernia treated at the Zainoel Abidin Regional General Hospital, Banda Aceh. Methods: Descriptive research with case studies through the nursing process approach from assessment, nursing diagnosis, planning, implementation, and evaluation. The subject of the study was 1 Pre-Operative Hernia Inguinalis Lateralis Sinistra patient who was treated in the internal medicine room who was given Slow Deep Breathing Exercise intervention. The research instruments used to collect data were medical surgical nursing care sheets and pain measuring instruments using the Numeric Rating Scale. Results: After implementing Slow Deep Breathing Exercise twice a day (duration 15 minutes during the intervention) for 3 days combined with oxygen therapy via nasal cannula (3 liters/minute), the patient's main problem, namely acute pain, decreased from a scale of 8 to 6 with all patient activities still being assisted. Conclusion: Based on the research results, it can be concluded that the patient's problem, namely acute pain, was partially resolved through the Slow Deep Breathing Exercise intervention because the pain still often occurs with an uncertain duration and interferes with the patient's basic needs.